2010
DOI: 10.1194/jlr.p000331
|View full text |Cite
|
Sign up to set email alerts
|

The National Niemann-Pick Type C1 Disease Database: correlation of lipid profiles, mutations, and biochemical phenotypes

Abstract: Niemann-Pick type C1 disease (NPC1) is an autosomal recessive lipid storage disorder characterized by clinical manifestations involving primarily the liver and brain ( 1 ). The onset of signs or symptoms can occur at any age and have a variable phenotype. The classic clinical phenotype is also variable and includes mid-to-late childhood onset of gait disturbance followed by progressive neurodegeneration with vertical gaze palsy, seizures, and dementia, resulting in death during the second or third decade ( 2-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 51 publications
8
62
1
Order By: Relevance
“…Compared with the age-and sex-matched unaffected reference population ( 16 ), NPC patients of our cohort were overrepresented in the lower 5th percentile group with regard to HDL-c, LDL-c, and free cholesterol, as well as above the 95th percentile with regard to triacylglycerides (TGs). This corroborates previous fi ndings that NPC patients have a higher probability for low HDL-c, LDL-c, and blood cholesterol levels, whereas TG levels tend to be increased ( 30 ). No evident differences between biochemically "variant" and "classic" NPC patients were found for LDL-c, cholesterol, and TG.…”
Section: The "Variant" Biochemical Npc Phenotype Correlates With Normsupporting
confidence: 80%
See 1 more Smart Citation
“…Compared with the age-and sex-matched unaffected reference population ( 16 ), NPC patients of our cohort were overrepresented in the lower 5th percentile group with regard to HDL-c, LDL-c, and free cholesterol, as well as above the 95th percentile with regard to triacylglycerides (TGs). This corroborates previous fi ndings that NPC patients have a higher probability for low HDL-c, LDL-c, and blood cholesterol levels, whereas TG levels tend to be increased ( 30 ). No evident differences between biochemically "variant" and "classic" NPC patients were found for LDL-c, cholesterol, and TG.…”
Section: The "Variant" Biochemical Npc Phenotype Correlates With Normsupporting
confidence: 80%
“…Although this may not be due to shortcomings of routine genomic sequencing in identifying deep intronic NPC1 mutations ( 5 ), one previous study reported a high coincidence of the "variant" cellular phenotype with no apparent defects in the NPC1 gene ( 39 ). Therefore, it is tempting to speculate that variants in additional, yet-unidentifi ed genes have an impact on the NPC cellular phenotype, and modifi ers of lysosomal cholesterol levels have been demonstrated in cell and animal models (e.g., 14,30,40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol levels in plasma samples from NPC patients were <200 mg/dl; i.e., within the normal range for adults as defi ned by the American Heart Association ( 80 ). These values are similar to those reported previously for NPC1 patients ( 81 ). Importantly, plasma levels of ␣ -tocopherol and the most prevalent vitamin E form in the US diet, ␥ -tocopherol, were within the clinically normal range (12-50 M) ( 82 ).…”
Section: Plasma Tocopherol and Cholesterol Levels In Npc-affected Micsupporting
confidence: 79%
“…Subsequent studies performed to determine the transferability of NPC1 obesity risk alleles have also discovered alleles associated with decreased fasting insulin levels and increased risk for type 2 diabetes independent of body weight in other populations [10][11][12] . These findings were noteworthy since NPC1 mutations were originally known to be responsible for a rare and fatal autosomal-recessive lipid-storage disorder called NPC1 disease [13,14] . With respect to this disease, the NPC1 derived and minor allele for 3182T>C encoding the Ile1061Thr residue predisposes to most diagnosed cases of NPC1 disease in the United States, particularly among Hispanic patients living in the Northern Rio Grande Valley region of New Mexico and Colorado [14] .…”
Section: Introductionmentioning
confidence: 94%
“…These findings were noteworthy since NPC1 mutations were originally known to be responsible for a rare and fatal autosomal-recessive lipid-storage disorder called NPC1 disease [13,14] . With respect to this disease, the NPC1 derived and minor allele for 3182T>C encoding the Ile1061Thr residue predisposes to most diagnosed cases of NPC1 disease in the United States, particularly among Hispanic patients living in the Northern Rio Grande Valley region of New Mexico and Colorado [14] . Population studies suggest that this NPC1 mutation may have resulted from a founder effect originating from Spanish descendants that migrated and settled in this region [15,16] .…”
Section: Introductionmentioning
confidence: 94%